Role of Dobutamine Stress Test and Speckle Tracking in Ischemic Heart Disease, Comparative Study - Marwa Majeed Kadhim; Shokry F. AL-Saad; Hassan Salim Al-Jumaily; Zainab Falah Hassan (Medical Journal of Babylon)
Background:Coronary artery disease (CAD) is a major cause of cardiovascular mortality. Echocardiography plays a vital role in early detection and treatment. Objectives:We investigated the use of speckle tracking during dobutamine stress echocardiography (DSE) to diagnose CAD in moderate-risk patients. Materials and Methods:A 4-month cross-sectional study enrolled 42 moderate-risk patients without prior CAD history. Data included questionnaires, echocardiographic measurements, and SPSS analysis. Results:Patients were divided into CAD-negative (66.7%) and CAD-positive (33.3%) groups based on coronary angiography. Speckle tracking during stress correlated better with angiography (kappa = 0.78) than at rest (kappa = 0.21) or stress visualization (kappa = 0.66). Sensitivity and specificity were 71.4% and 92.8% (stress test), 57.1% and 85.7% (speckle at rest), and 85.7% and 92.8% (speckle during stress), respectively. Conclusion:Speckle tracking during DSE is a promising approach for diagnosing CAD in moderate-risk patients, enhancing early intervention possibilities.